Effects of glyphosate on nodulation and nitrogen fixation of transgenic glyphosate-tolerant soybean - Corral, Raúl Alejandro (2022)
Background: The use of glyphosate on glyphosate-tolerant soybean crops led to improved control of a wide range of weeds, which resulted in reduced costs with the no-till system. The emergence of the first herbicide-resistant weeds have driven an increase in glyphosate applications, and even though those soybean materials have a low sensitivity to glyphosate, the rhizobial symbionts could be affected by the herbicide, and plants might be indirectly injured. Objective: This study aimed to determine the effect of multiple glyphosate applications throughout the soybean crop cycle on plant growth, nodulation and biological nitrogen fixation (BNF). Methods: The effects of one, two and three treatments of a recommended dose of glyphosate on BNF and growth of glyphosate-tolerant soybean plants were evaluated in greenhouse and field experiments. Results: Two or more applications of glyphosate inhibited the BNF and growth of soybean plants. Under controlled conditions, at least one glyphosate application at V1 affected the number and mass of nodules per plant, and successive applications in advanced phonological stages resulted in the inhibition of nodule growth. With two and three sprayings of glyphosate, the proportion of N derived from the air in plants was reduced by 41% compared with the treatment without glyphosate. In field experiments, detrimental effects of three sequential applications of glyphosate on number of nodules per plant (-25%), biomass production (-21%) and grain yield (-36%) were detected. Conclusions: Multiple glyphosate applications of glyphosate inhibited the BNF and growth of soybean plants and it could be as damaging as +weed interference. Nomenclature: Glyphosate; soybean, Glycine max (L.) Merril.